Development of E-Modules of Hydrology Cycle Integrated With Verses of The Qur'an: A Needs Analysis Review - Muhammad Khairul,; Dede Rohmat ,; Nurul Fajri Saminan , (Jurnal Serambi Ilmu, 2026)
Water resources constitute a pivotal facet of human existence and environmental equilibrium, particularly within the purview of geography. In 21st-century education, the imperative is to impart contemporary and germane insights into the hydrological cycle through innovative pedagogical methodologies and media. A cornerstone of innovative learning lies in the provision of adaptable educational resources, furnishing an efficacious alternative to augment students' comprehension of scholastic materials. The integration of Quranic verses in geography education emerges as a stratagem to endow students with supplementary value, instilling moral and ethical perspectives on the stewardship of natural resources. Consequently, this study adopts a qualitative descriptive research methodology, employing questionnaires disseminated to 30 students and 2 teachers. Subsequent data analysis reveals a conspicuous demand for the development of geography learning e-modules, with a specific emphasis on integrating Quranic verses into hydrological cycle materials. Foreseen as instrumental, these e-modules are poised to facilitate students' apprehension of abstract phenomena intrinsic to geography education, where visual comprehension is frequently challenging. The assimilation of e-modules is anticipated to underpin a profound understanding of intricate topics, exemplified by the nuanced dynamics of the rain phenomenon within the Hydrosphere.